(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Psychological effects (anxiety) are part of the post-COVID-19 syndrome. These symptoms may persist from the initial illness or develop after recovery, affecting the patient’s ability to perform daily activities. Objectives: Determining the anxiety status of patients after Covid-19 treatment at Agricultural General Hospital in 2022 and some related factors. Methods: Cross-sectional survey, quantitative research. Results: The study collected information from 400 patients after Covid-19 treatment at Agriculture General Hospital through a questionnaire. The study results showed that the rate of patients feeling anxiety was 69,5%, of which 14,8% of patients with mild anxiety and 25,3% of patients with severe anxiety. The factor related to patient’s anxiety includes: education, employment, income, economic change, living status, living with children under 18 years old, post-covid-19 infection, source of Covid-19 infection, treatment level, comorbidities and hospital landscape (p<0.05).